Persepsi Ujaran Manusia dalam Psikolinguistik - Mukhlishin, Muh. Irfan (FKIP Universitas Wisnuwardhana, 2023)
Psycholinguistic research on human speech perception has become a major focus in understanding how humans process and understand spoken language. This study aims to investigate the way in which individuals perceive human speech, taking into account factors such as segmentation, word recognition, and understanding of meaning. Experimental methods are often used, including speech processing experiments, discontinuous speech comprehension experiments, and neuroimaging techniques such as functional MRI. The research results show that human speech perception is influenced by various factors, including linguistic and non-linguistic context, as well as the individual's ability to interpret audio information. The implications of this research are not only relevant in the fundamental understanding of how language works, but are also important in the development of speech recognition technology, speech therapy, and other language interventions. With a better understanding of how humans perceive speech, we can improve various aspects of spoken communication, including language teaching, therapeutic communication, and more effective user interface design.